PERAN SISTEM FlBRINOL1S1S PADA BERBAGAI PROSES FISIOLOGIS DAN PATOLOGIS - Gde Budhiarta, Anak Agung (journal of internal medicine, 2006)
Plasminogen can be converted to plasmin either by t-PA or u-PA. A dual role for these pathways isnow well established where t-PA is involved in fibrin homeostasis and u-PA is primarily involved in cellmigration and tissue remodelling. Using this mechanism thrombolytic terapy of myocardial infarction andsome other thromboembolic diseases have been introduced. Thrombolytic therapy could be improved byearlier and accelerated treatment, the used of plasminogen activator with increased thrombolytic potencysuch as reteplase, tenetecplase and staphylokinase and the use of more specific and potent anticoagulant andantiplatelet agents. Increased activity of matrix metalloproteinases (MMPs) has been implicated innumerous disease processes, including tumor growth and metastases, arthritis, and periodontal disease. It isnow becoming increasingly clear that extracelluler matrix degradation by M M Ps is also involved in thepathogenesis of cardiovascular disease, including atherosclerosis, restenosis, dilated cardiomyapathi,andmyocardial infarction. Administration of synthetic MMP inhibitor in experimental animal models of; thesecardiovascular disease significantly inhibits the progression of respectivelyatherosclerotic lesion formation,neointima formation, left ventricular remodeling, pump dysfunction, and infarc healing.